Outbreak of Type E Botulism Associated with Home-cured Ham Consumption - Rosetti, F. (1999)
Fil: Rosetti, Francisco. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología; Argentina.